Implementasi Kepemimpinan Transformasional Dan Berbasis Nilai Dalam Pengembangan Mutu Di Era Digital 5.0 - Umroatin, Yuli (Advances in Humanities and Contemporary Studies, 2023)
The digital era is a situation where humans can find various information and communication via the internet. On the one hand, this condition is a pleasant thing, which is to prove that the times have changed in a more advanced direction. With the existence of Islamic education in this digital era, it aims to form a competent successor of the nation, a Muslim who has a lot of knowledge and skills so that he can live a good, safe, prosperous and happy life. The purpose of this study was to analyze the patterns, strategies and results of achieving transformational and value-based leadership in the development of the quality of the digital era 5.0 in Wali Songo islamic boarding school, Ngabar Ponorogo. Problem formulation: (1) Transformational and values-based leadership patterns in the development of the quality of the Digital 5.0 era in Tarbiyatul Mu'allimin and Mu'allimat al-Islamiyyah Pondok Pesantren Wali Songo Ngabar Ponorogo. (2) Transformational and value-based leadership strategies in developing the quality of the digital era 5.0 in Wali Songo islamic boarding school, Ngabar Ponorogo. (3) The results achieved in Transformational and values-based leadership in the development of the quality of the digital era 5.0 in Wali Songo islamic boarding school, Ngabar Ponorogo. The type of research used is qualitative research, which is a study that chooses natural characteristics (natural setting) as a direct data source, descriptive process, and in data analysis qualitative research tends to be carried out by inductive analysis and is an important thing. The results of the study: (1) The leadership pattern is transformational or visionary, has clear directions and goals, is forward-looking to move forward and applies TQM to make improvements and improvements every year. (2) The leadership strategy applied is Transformational leadership, namely leaders who try to invite, and motivate all elements of stakeholders to carry out all activities for developing the quality of education at the Wali Songo Islamic boarding school, Ngabar, especially Tarbiyatul Mu'allimin and Mu'allimat al-Islamiyyah. The implementation of the leadership strategy is the plan, do, check, and action. (3) The results achieved from Transformational and values-based leadership in Tarbiyatul Mu'allimin and Mu'allimat al-Islamiyyah are the development of educational facilities and infrastructure, Successfully implementing an integration of the Islamic boarding school curriculum and the general curriculum, increasing the competence and quality of educators, increasing the quality of students, the development of small and medium-sized Islamic boarding schools.